2008
DOI: 10.1073/pnas.0712361105
|View full text |Cite
|
Sign up to set email alerts
|

A translocation causing increased α-Klotho level results in hypophosphatemic rickets and hyperparathyroidism

Abstract: Phosphate homeostasis is central to diverse physiologic processes including energy homeostasis, formation of lipid bilayers, and bone formation. Reduced phosphate levels due to excessive renal loss cause hypophosphatemic rickets, a disease characterized by prominent bone defects; conversely, hyperphosphatemia, a major complication of renal failure, is accompanied by parathyroid hyperplasia, hyperparathyroidism, and osteodystrophy. Here, we define a syndrome featuring both hypophosphatemic rickets and hyperpara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
151
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(159 citation statements)
references
References 39 publications
3
151
5
Order By: Relevance
“…This patient has a de novo germline translocation involving the region upstream of the KL (Klotho) gene, which probably accounted for her congenital elevation of plasma α-Klotho level and hypophosphatemic rickets. 35 At age 30, two tumors were found in her bilateral mastoid bones, confirmed histopathologically to be phosphaturic mesenchymal tumors, and shown by CISH to express elevated levels of FGF23. Both tumors were fusion-negative and the one tested by immunohistochemistry showed diffuse and weak expression of FGFR1 and FGF1.…”
Section: Discussionmentioning
confidence: 89%
“…This patient has a de novo germline translocation involving the region upstream of the KL (Klotho) gene, which probably accounted for her congenital elevation of plasma α-Klotho level and hypophosphatemic rickets. 35 At age 30, two tumors were found in her bilateral mastoid bones, confirmed histopathologically to be phosphaturic mesenchymal tumors, and shown by CISH to express elevated levels of FGF23. Both tumors were fusion-negative and the one tested by immunohistochemistry showed diffuse and weak expression of FGFR1 and FGF1.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies showed that overexpressing Klotho by viral-based gene transfer 34 or genetic manipulation 33 attenuated progressive renal injury, but the Klotho status and systemic complications of CKD were not studied. Because Klotho is present in multiple body fluids, 25,27,36,57 the restoration of Klotho clearly exerts multiple systemic effects in addition to renoprotection.…”
Section: Pathogenic Role Of Klotho In Progression Of Ckd and Its Compmentioning
confidence: 99%
“…Rare human cases of profound KL protein alterations result in life-threatening disorders including hypophosphatemic rickets (Brownstein et al 2008) and tumoral calcinosis (Ichikawa et al 2007) with decreased and increased KL protein, respectively. As well, KL polymorphisms, resulting in more subtle alterations in KL protein level or function, affect lifespan and the risk of disease development (Kuro-o 2009).…”
mentioning
confidence: 99%